Management Of Reading Community Pelosok Bumi In Karawang Regency - Anas Muthtar; Hidayat Hidayat; Ahmad Syahid (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
Aims to describe planning, organizing, and supervising reading community. The concept of George Robert Terry (2007:31) "Management as a typical process, carried out to determine and achieve the goals that have been set by the use of human resources and other resources." Qualitative research approach. Data collection techniques are observation, interviews, and documentation. The research subjects were one manager, one volunteer, and two residents student of reading community Pelosok Bumi, Karawang. Analysis of the research obtained there are four stages in the management begins with the identification of learning needs in the planning stage. Organizing is done by grouping the teaching staff into study groups. The implementation started on Saturday. The media, the strategies and methods used were returned to the volunteers. Supervision is carried out by going directly into the study group and immediately after the implementation there is a learning evaluation meeting. Suggestions Institutions can add volunteers so that the learning situation can be conducive.Keywords: Management, Reading Community